Bivalves da Formação Taciba, Cisuraliano, Grupo Itararé, Bacia do Paraná, e seu significado bioestratigráfico e paleoambiental no contexto da glaciação neopaleozóica no Gondwana central - Neves, Jacqueline Peixoto [UNESP] (2013)
At the Teixeira Soares County, Paraná State, the uppermost portion of the Taciba Formation (~60 m thick), Itararé Group, is dominated by massive to laminated, matrixsupported conglomerates, representing re-sedimented polymitic diamictites. This is succceded by fine to medium-grained sandstone with tabular cross stratification and shell pavements, interpreted as nearshore deposits. Above, laminated and intensely bioturbated siltstones with articulated shells, probably deposited in inner shelf settings occur. To the top, amalgamated, fine to very fine sandstone/siltstone with low-angle cross-stratification or hummocky cross-stratification and intercalated mudstones, including in situ shells, are interpreted as stacked storm deposits, in distal shoreface environments. Finally, massive to laminated siltstone/mudstone or gray shales are inferred as outer shelf deposits (Passinho shale), which are capped by fluvio-deltaic sediments of the Rio Bonito Formation. This finning upwards succession characteristically lacks any dropstones or ice-rafted debris, and is associated to the Late Paleozoic post-glacial transgression. Six distinct, bivalve-rich assemblages were identified, reflecting changes in paleoenvironmental parameters. Ninteen species were described, including four new. Myonia argentinensis, Atomodesma (Aphanaia) orbirugata and Heteropecten paranaensis indicate correlation with assemblages of the Bonete Formation, Sauce Grande Basin, Argentina, indicating a possible Late Asselian–Sakmarian age. Members of the icehouse-style Eurydesma– Trigonotreta biota are lacking